Next endoscopic approach for acute lower gastrointestinal bleeding without an identified source on colonoscopy: upper or capsule endoscopy? - Aoki, Tomonori; Nagata, Naoyoshi; Yamada, Atsuo; Shimbo, Takuro; Matsushita, Yuuki; Shimomura, Akira; Kobayashi, Sakurako; Moriyasu, Shiori; Niikura, Ryota; Sakurai, Toshiyuki; Hirata, Yoshihiro; Akiyama, Junichi; Uemura, Naomi; Koike, Kazuhiko (Endoscopy International Open, 2019)
Background and study aims We evaluated the utility of esophagogastroduodenoscopy (EGD) or capsule endoscopy (CE) as the next diagnostic approach after negative colonoscopy (CS) results in acute-onset hematochezia.Patients and methods We retrospectively analyzed 401 patients emergently hospitalized for acute hematochezia who underwent CS within 48 hours of arriving at two large emergency hospitals and in whom a definitive bleeding source was not identified. The positive endoscopic findings, requirement for additional therapeutic procedures, and 30-day rebleeding rates were compared among three strategies: EGD following CS (CS-EGD), CE following CS (CS-CE), and CS alone. Predictors of positive endoscopic findings in the CS-EGD strategy were determined.Results The rates of positive endoscopic findings and requirement for additional therapeutic procedures were 22 % and 16 %, respectively, in CS-EGD and 50 % and 28 % in CS-CE. The 30-day rebleeding rate did not significantly decrease in CS-EGD (8 %) or CS-CE (11 %) compared with CS alone (12 %). The rate of additional endoscopic therapies was lower in patients with a colonic diverticulum than in those without (CS-EGD: 3 % vs. 33 %, P = 0.007; CS-CE: 11 % vs. 44 %, P = 0.147). A history of syncope, low blood pressure, blood urea nitrogen/creatinine ratio of ≥ 30, and low albumin level significantly predicted EGD findings after negative CS results (P < 0.05).Conclusions When the definitive bleeding source is not identified by colonoscopy in patients with acute hematochezia, adjunctive endoscopy helps to identify the etiology and enables subsequent therapy, especially for patients without a colonic diverticulum. Upper gastrointestinal endoscopy is indicated for severe bleeding; other patients may be candidates for capsule endoscopy.